The Euroarea: Premature, diminished, divergent - Mario Nuti (Transformation, Integration and Globalization Economic Research (TIGER), 2013)
The main causes of the current Euro crisis are: 1) its premature birth, before the earlier stages of political and fiscal integration, and integration of defense and foreign policy; 2) the diminished nature of the European Central Bank, which is not only independent, like the Fed, the Bank of England or the Central Bank of Japan, but also - unlike those sister institutions - forbidden to purchase government bonds; and 3) the increasing divergence of the monetary, fiscal and real parameters of the member states. An exit from the Euroarea would not provide a solution to the crisis, because of the tight fiscal discipline to which exiting Euro members would still be subjected, and the high cost of leaving the EU altogether. It seems preferable to promote further progress towards the creative evolution of the ECB, and the relaxation of EU austerity, perhaps threatening such an exit with vigour and persistence.
Keywords: 330